Religious Potential in the protection of Forest Ecosystems - Sadowski, Ryszard F. (Studia Ecologiae et Bioethicae, 2012)
The shrinking area of forests urges intensification of efforts to restore damaged forest ecosystems and protect the existing ones. Religions may become an important ally in this process. Their ecological potential remains under-exploited. Owing to their „ecological advantages”, i.e. their capacity to shape cosmologies (worldviews), their moral authority and a broad base of adherents, significant material resources, and community-building capacity, religions can help shape ecological lifestyles. All major religious traditions have a lot to offer. Evoking religious motivations of a substantial part of humanity can greatly improve the condition of forests, increase the effectiveness of their protection, and encourage broad sections of societies to get involved in this task.